Annotated Copies of Early Editions of Johnson's Dictionary: A Preliminary Account. (10th June 2021) - Considine, John
Abstract: Early responses to Johnson's Dictionary of the English Language included manuscript annotations, sometimes very extensive, in copies of the dictionary. This article surveys twenty-one copies of eighteenth-century editions of the dictionary with critical or informative annotations, bearing on etymology or usage, adding new words or senses, or improving the supply and referencing of quotations. Some of these copies are extant in institutional or private collections, and others are unlocated. The annotators include Johnson himself; members of his circle including Edmund Burke, Samuel Dyer, Edmond Malone, Hester Piozzi, and George Steevens; and other readers including Leigh Hunt, Horne Tooke, Noah Webster, and John Wilkes.